Advances in drug delivery systems utilizing blood cells and their membrane-derived microvesicles - Andong He; Yuye Huang; Chao Cao; Xuejin Li (Taylor & Francis Group, 2024)
The advancement of drug delivery systems (DDSs) in recent decades has demonstrated significant potential in enhancing the efficacy of pharmacological agents. Despite the approval of certain DDSs for clinical use, challenges such as rapid clearance from circulation, toxic accumulation in the body, and ineffective targeted delivery persist as obstacles to successful clinical application. Blood cell-based DDSs have emerged as a popular strategy for drug administration, offering enhanced biocompatibility, stability, and prolonged circulation. These DDSs are well-suited for systemic drug delivery and have played a crucial role in formulating optimal drug combinations for treating a variety of diseases in both preclinical studies and clinical trials. This review focuses on recent advancements and applications of DDSs utilizing blood cells and their membrane-derived microvesicles. It addresses the current therapeutic applications of blood cell-based DDSs at the organ and tissue levels, highlighting their successful deployment at the cellular level. Furthermore, it explores the mechanisms of cellular uptake of drug delivery vectors at the subcellular level. Additionally, the review discusses the opportunities and challenges associated with these DDSs.